Design And Analysis Of Modified-Proportional Fair Scheduler For LTELTE-Advanced - Ismail, Mohd Khairy (2016)
Nowadays, Long Term Evolution-Advanced (LTE-Advanced) is well known as a cellular network that can support very high data rates in diverse traffic conditions. One of the key components of Orthogonal Frequency-Division Multiple Access (OFDMA), Radio Resource Management (RRM), is critical in achieving the desired performance by managing key components of both PHY and MAC layers. The technique that can be done to achieve this is through packet scheduling which is the key scheme of RRM for LTE traffic processing whose function is to allocate resources for both frequency and time dimensions. Packet scheduling for LTE-Advanced has been a dynamic research area in recent years, because in evidence, the increasing demands of data services and number of users which is likely to explode the progress of the LTE system traffic. However, the existing scheduling system is increasingly congested with the increasing number of users and requires the new scheduling system to ensure a more efficient data transmission. In LTE system, Round Robin (RR) scheduler has a problem in providing a high data rate to User Equipment’s (UEs). This is because some resources will be wasted because it schedules the resources from/ to UEs while the UEs are suffering from severe deep fading and less than the required threshold. Meanwhile, for Proportional Fair (PF) scheduler, the process of maximizing scheme of data rate could be very unfair and UE that experienced a bad channel quality conditions can be starved. So, the mechanism applied in PF scheduler is to weight the current data rate achievable by a UE by the average rate received by a UE. The main contribution of this study is the design of a new scheduling scheme and its performance is compared with the PF and RR downlink schedulers for LTE by utilizing the LTE Downlink System Level Simulator. The proposed new scheduling algorithm, namely the Modified-PF scheduler, divides a single sub-frame into multiple time slots and allocates the resource block (RB) to the targeted UE in all time slots for each sub-frame based on the instantaneous Channel Quality Indicator (CQI) feedback received from UEs. Besides, the proposed scheduler is also capable to reallocate RB cyclically in turn to target UE within a time slot in order to ensure the process of distributing packet data consistently. The simulation results showed that the Modified-PF scheduler provided the best performance in terms of throughput in the range of up to 90% improvement and almost 40% increment for spectral efficiency with comparable fairness as compared to PF and RR schedulers. Although PF scheduler had the best fairness index, the Modified-PF scheduler provided a better compromise between the throughput in /spectral efficiency and fairness. This showed that the newly proposed scheme improved the LTE output performances while at the same time maintained a minimal required fairness among the UEs.